Incidence of bronchiectasis concerning tuberculosis epidemiology and other ecological factors: A Korean National Cohort Study - Choi, Hayoung (ERJ Open Res, 2020)
In South Korea, the estimated incidences of bronchiectasis were 147–229 cases per 100000 with a decreasing trend. It may follow the concurrent decrease in the TB prevalence and incidence, and favourable personal and socioeconomic conditions. https://bit.ly/32UA8xH